Analisa Tingkat Efisiensi Perbankan Syari'ah dan Konvensional dengan Menggunakan Data Envelopment Analysis - Sudarsono, Heri (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2012)
This research utilises the non-parametric frontier approach, data envelopment analusis (DEA). By using such a analysis, the purpose of this studi is to analyse Islamic banking efficiency with the data during 2007-2010 covering 3 Islamic bank in Indonesia. In general, the result of study indicates that the level of efficiency of Islamic bank is various moving over time. In intermediary efficiency, conventional bank is found to be more efficient than Islamic bank. Moreover, conventional bank is more efficient than islamic bank. Since the study pinpoints the sources of inefficiency, it also helps to provide the banks with strategic planning.